Tool orientation optimization for 5-axis machining with C-space method. Issue 5 (February 2017) - Mi, Zhenpeng; Yuan, Chun-Ming; Ma, Xiaohui; Shen, Li-Yong
Abstract Collision avoidance is a fundamental problem in five-axis tool path planning. A two-step frame is widely used in tool path generation, that is, to determine C-spaces and then to design collision free pathes in the C-spaces. We present a feasible C-space computation algorithm for triangular mesh models based on collision-cone computation and stereographic projection. Then we sample points in the free area at each CC point and generate a tool orientation using the graph-based method. We also introduce a difference graph to find a smoother tool orientation. Experimental results show that the accelerations and velocities of the rotation axes are much smoother than those given by Plakhotnik and Lauwers (Int J Adv Manuf Technol 74:307–318, 2014).